Democratic policing in a changing world - Manning, Peter K. (Paradigm Publishers, 2010)
Defining democratic police and policing -- Police in the socio-political world -- Policing according to the difference principle -- Studying democratic policing -- Structural features of American policing -- Theorizing policing: recent efforts -- The reform of policing -- Practice and poesis: tactical poetry -- The dynamics and stability of modern policing -- Non-democratic policing